Coupled electrical-thermal-pyrolytic analysis of carbon fiber/epoxy composites subjected to lightning strike - Dong, Qi; Guo, Yunli; Sun, Xiaochen; Jia, Yuxi (Polymer (Guilford), 2015)
The high Joule heating of carbon fiber reinforced polymer composites (CFRP) subjected to lightning strike induces resin decomposition and carbon sublimation. The mechanism and characteristics of the change in composite material properties are the key basis of the numerical analysis and the optimal design of composite structures. In order to elucidate the damage phenomena caused by lightning strike, a tightly coupled electrical-thermal-pyrolytic analysis is conducted by introducing the numerical calculation of resin pyrolysis degree on the basis of thermal-electrical numerical analysis. Hence the electrical and thermal properties in both out-plane and in-plane directions are modeled as functions of the pyrolysis degree of the composite material, namely the material properties change with the component during the decomposition, which is revealed to be reasonable from both the numerical and the experimental results. The research is helpful for understanding the complicated relationships in the important damage process including electrical, thermal and chemical phenomena. [Display omitted] •The composite electrical-thermal-pyrolytic correlation analysis is performed.•The lightning strike damage can be estimated by temperature and pyrolysis degree.•The contour of the pyrolysis degree is inherited from the contour of temperature.